HUBUNGANTINGKAT PENGETAHUAN KEPALA KELUARGA TENTANG PENGGUNAAN AIR BERSIH TERHADAP KEJADIAN DIARE DI BANDAR PANDUANG KELURAHAN TANAH GARAM KOTA SOLOK TAHUN 2021 - Narmanda Tri Murti Ningsih; Farras Yufebrisa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Diarrhea is a major cause of morbidity and death in developing countries like Indonesia. This disease is closely related to the provision and use of clean water for the community in improving environmental health or public health in order to reduce the incidence of disease. The phenomena obtained by researchers in Tanjung Gadang Kenagarian are that there are still many people who use river water for daily needs, such as washing, bathing, defecating and also as a source of drinking water. The purpose of this study was to determine the relationship between the level of knowledge of the head of the family and the use of clean water on the incidence of diarrhea. In this study the research design used was cross sectional with a population of 215 families in Bandar Panduang Kelurahan Tanah Garam Kota Solok, while the sample was 68 families. Data collection used questionnaires and guided interviews, as well as data processing using computerization. The results of the univariate study found that 44% of respondents had low knowledge and 56% of respondents had high knowledge about the use of clean water. Most of the respondents (72%) had experienced diarrhea. The results of the bivariate study found a significant relationship between the level of knowledge and the incidence of diarrhea (p value = 0.020 and OR = 4.728). Based on the results of the research above, it is hoped that health workers can provide more intensive counseling about diarrheal diseases and for the community to be able to adopt a healthy lifestyle.Keywords: Family Knowledge, Use of Clean Water, Diarrhea